The Effect of Guided Inquiry Learning Models on Students’ Critical Thinking Skills and Learning Outcomes in Science Subjects at MTs Miftahul Muin - Nur Asiah (Universitas Muhammadiyah Makassar, 2021)
This study aims to find out the effect of Guided Inquiry Learning Model on students’ critical thinking skills and learning outcomes on the concept of system of force and motion for class VIII MTs Miftahul Muin. This research is a Quasi Experimental research, with Pretest-Posttest Non-Equivalent Control Group Design. cluster random sampling technique involving two groups: one experimental group that received learning treatment using guided inquiry learning models and one control group treatment using conventional learning models. The research data were obtained through multiple-choice tests to measure students’ learning outcomes and essay tests to measure students' critical thinking skills. To analyze the data, the non-parametric inferential statistics were used. Measurements include a prerequisite analysis test and hypothesis testing. The prerequisite test analysis consists of normality and homogeneity tests. Hypothesis testing used ANCOVA with SPSS 20.0 for windows at a significance level of 0.05. The results of data analysis obtained that the corrected experimental class average value for learning outcomes was 37.12 and critical thinking skills was 35.69, while the corrected average value of the control class learning outcomes was 15.20 and critical thinking skills were 16, 63 with a significant level α 0.05, that is, where the deficiency has p (0.000) 0.05. The results showed a significant effect of the guided inquiry model on critical thinking skills and learning outcomes of class VIII students of MTs Miftahul Muin